DISCOURSE OF MEMORY: HISTORICAL AND PHILOSOPHICAL ASPECT OF RESEARCH - Суходуб, Т. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article describes the concept of memory, formed in the history of philosophy and modern culture. Emphasizes interdisciplinary as the main methodological principle in the study of problematics of memory. The conclusion is that modern culture shows not only an interest of past experience of memory, but also search of “new” practice of memory